Islamic Environmentalism in Indonesia: An Analytical Study of MUI Fatwas on Environmental Protection - Iskandar Iskandar; Hadi Sofuoğlu (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2025)
This study investigates the role of Islamic environmental ethics, as articulated by the Indonesian Ulema Council (MUI), in fatwas on environmental protection. Indonesia, with its large Muslim population, faces significant ecological issues, including climate change, forest burning, and resource depletion. Recognizing the urgency of these problems, MUI has issued several fatwas on topics such as environmentally friendly mining, wildlife conservation, waste management, forest burning, and climate change. This research aims to assess the effectiveness of these fatwas in fostering sustainable environmental practices among Indonesian Muslims, examining their alignment with Islamic teachings and their impact on public attitudes, behaviors, and policy. This study employs a qualitative research design, utilizing document analysis and content analysis to explore the content and reception of MUI’s fatwas. By analyzing the fatwas’ theological foundations and practical implications, the research seeks to understand how Islamic environmental principles can mobilize religious communities to protect the environment. The results indicate that the fatwas are structured around Islamic principles, citing Qur'anic verses, Hadiths, and scholarly opinions, and provide recommendations for various stakeholders, including government officials, communities, and entrepreneurs. These fatwas emphasize collaborative efforts and advocate for responsible resource use and conservation, demonstrating that Islamic environmental ethics offer a valuable framework for addressing Indonesia’s environmental crises and promoting sustainable practices.